Correlation between Pacifier Use in Preterm Neonates and Breastfeeding in Infancy: A Systematic Review - Eirini Orovou; Maria Tzitiridou-Chatzopoulou; Maria Dagla; Panagiotis Eskitzis; Ermioni Palaska; Maria Iliadou; Georgios Iatrakis; Evangelia Antoniou (MDPI AG, 2022)
Background: Breastfeeding is very important for the proper nutrition and growth of the child, as well as, the health of the mother. To start breastfeeding, the neonate must have extensive oral capacities for sucking functions but, premature neonates may not have the muscle strength needed to suck successfully. However, the non-nutritive sucking achieved by using a pacifier, has been identified by previous research as a factor associated with shorter duration and exclusivity of breastfeeding. This study aims to perform a systematic review to investigate the relationship between pacifier use in preterm neonates and breastfeeding in infancy. Methods: We included prospective studies, as well as randomized controlled studies that evaluated the association between pacifier use by preterm neonates and of breastfeeding in infancy. Ten research articles from PubMed/Medline, Google Scholar and Crossref were included in the review from a total of 1455 articles. The results differ depending on the type of study.Most prospective studies have shown a negative correlation between pacifier use and breastfeeding, while the randomized controlled studies found a positive correlation. Conclusions: Pacifier use in preterm infants helps transition from tube to oral feeding, breastfeeding, faster weight gain and earlier discharge from the NICU. However, the relationship between pacifiers and breastfeeding is more complicated, as it appears to be influenced by additional risk factors.